Efavirenz Plasma Concentrations and HIV Viral Load in HIV/AIDS-tuberculosis Infection Patients Treated with Rifampicin - Nina Mariana; Purwantyastuti Purwantyastuti; Instiaty Instiaty; Adria Rusli (Acta Medica Indonesiana)
Aim:to determine the effect of a rifampicin-containing tuberculosis regimen on efavirenz plasma concentrations and viral load in HIV/AIDS-Tuberculosis infection patients who received efavirenz-based antiretroviral therapy. Methods:plasma efavirenz concentrations and HIV viral load were measured in HIV/AIDS patients treated with 600 mg efavirenz-based antiretroviral for 3 to 6 months and in HIV/AIDS-Tuberculosis infection patients treated with similar antiretroviral regimen plus rifampicin-containing antituberculosis in Sulianti Saroso Infectious disease Hospital, Jakarta. Plasma efavirenz concentration in both groups were compared using Mann-Whitney test, while proportion of patients with viral load >40 copy/mL were analyzed with chi-square test. Results:forty five patients (27 with HIV/AIDS and 18 with HIV/AIDS-Tuberculosis infections) were recruited during the period of February to May 2015. The median efavirenz plasma concentration obtained from HIV/AIDS group was 0,680 mg/L(range 0,24 to 5,67 mg/L and that obtained from HIV/AIDS-Tuberculosis group was 0.685 mg/L (0.12 -2.23 mg/L) which was not significantly different statistically. The proportion of patients with viral load ≥40 copies/mL after 3-6 months of ARV treatment in the HIV/AIDS group was 51.9%, and in the HIV/AIDS-Tuberculosis group was 72.2%, which was not significantly different statistically (Chi Square test, p=0.291). Conclusion:plasma efavirenz concentration in HIV/AIDS-tuberculosis patients receiving antiretroviral and rifampicin is not significantly different from that on HIV/AIDS patients without tuberculosis. Proportion of patients with viral load of >40 copy/mL is higher in HIV/AIDS-tuberculosis patients receiving rifampicin compared to HIV/AIDS patients that not receive rifampicin. However, this difference did not reach statistical significance. Confirmatory studies with bigger sample size are needed to clarify the influence of rifampicin on plasma level ofefavirenzand and on viral load.